Localized hypertrichosis with traumatic panniculitis: A case report and literature review - Monthanat Ploydaeng (2020)
© 2019 The Author(s). Published by S. Karger AG, Basel. Localized hypertrichosis with traumatic panniculitis is considered a rare condition. Previous articles have reported occurrence in females aged between 20 and 35 years. Possible mechanisms of trauma-induced localized hypertrichosis include hyperemia and angiogenesis induced by local inflammation, which can alter the hair growth cycle. The presence of inflammatory cells and lipomembranous changes on histopathology can support the diagnosis. We herein present a 35-year-old female patient with localized hypertrichosis following blunt trauma.